Optimization of the foot/pedal system through custom-molded carbon shoes for the sprinters of the french national track cycling team - Couveinhes, A.; Brunet, E.; Rao, G.; Retalli, M.; Sachet, I.; Giraud, F.; Soulaine, G. (Journal of Science and Cycling, 2025)
This study aims to optimize the foot/pedal system ergonomics for world-class and elite international track cycling sprint specialists. Over the past decade, sprinters have been using custom-molded carbon shoes that do not adhere to any standardized optimization for the foot/pedal interface. The various foot-molding techniques used to date differ from one another and do not allow for the integration of orthopedic corrections. 70% of the French sprint team experienced non-traumatic lower limb injuries. The nature of these pathologies suggests the need for podiatric intervention, leading us to identify actual carbon-molded shoes as a potential cause. Currently, no studies have been conducted to validate any performance benefits of these custom-molded carbon shoes with orthopedic corrections for athletes. The challenges faced by elite sprint cyclists require optimizing power transfer between the rider and the bike while also preventing injuries due to the high levels of mechanical stress. The objective of our study was to determine whether the development of carbon-molded shoes with proper biomechanical consideration for each athlete could reduce the risk of injury and improve performance.